What is the Relationship between the Four Dimensions of the Balanced Scorecard and Organization Performance of Ghanaian Public Universities? - Nyukorong, Remy (European Scientific Journal, ESJ, 2022)
The Balanced Scorecard (BSC) is one of the best-known strategic planning and evaluation tools that uses both monetary and non-monetary data. This paper focuses on empirically testing whether the four dimensions of the BSC predicts organizational performance of Ghanaian public universities. The study adopted a cross-sectional, descriptive survey design and the primary sources of data was gathered through hand-administered structured questionnaires from both academic and administrative staff of 10 accredited public universities in Ghana. The study also employed structural Equation Model (SEM) with SmartPLS to analyze 134 samples. Results of the boostrapping method for the structural model and the t-values of the four dimensions of the BSC were significantly and statistically different from each other, but all showed a positive relation on perceived organizational performance. The results showed that non-financial measures have better outcomes for employees’ performances which corroborates the central proposition of the Balanced Scorecard. It is recommended that public universities that want to maintain and improve organizational performance must pay attention to the customers’ perspective by providing relevant and high-quality education that acquaints students with knowledge and transferable basic skills and also identify opportunities for special initiatives, collaborative partnerships, and accountability to constituents.